Comparative Performance of Different Types of Pneumatic Tyres Used in Camel Carts under Sandy Terrain Condition - Tiwari, G S (Annals of Arid Zone, 2016)
Considerable amount of energy is lost due to use of improper tyre design and other related parameters. Four animal drawn vehicle (ADV) tyres of 5.00-19, 6.00-19, 7.00-19, and 8.00-19 size and two types of automobile discarded tyres of size 9.00-20 were selected to test their performance under controlled soil bin conditions in sand. These tyres were tested at five normal loads of 200, 400, 600, 800 and 1000 daN in the draught capacity of camels. Inflation pressure varied from 172.5 to 379.5 kPa for the ADV tyres and 69 to 345 kPa for automobile discarded tyres. A tyre test carriage was used to mount the test wheels of different sizes. Performance of the wheels was evaluated on the basis of towing force at forward speed of 3.1 km h-1 . The performance of the automobile discarded tyres was found superior to that of ADV tyres on the basis of reduced rolling resistance. Key words: Camel cart, tyre, ADV, inflation pressure, normal load and rolling resistance.